Hubungan Dukungan Keluarga dan Dukungan Teman Sebaya dengan Tingkat Stres pada Mahasiswa Sarjana Keperawatan dalam Menghadapi Tugas Akhir di Universitas ‘Aisyiyah Surakarta - Nanda Dhona Bhertayana; Eska Dwi Prajayanti (Jurnal Anestesi, 2024)
Stress occurs when someone experiences difficulties in their life caused by internal and external factors which every human being must experience, including students. Students' relationships with close people around them, such as family and peers, influence students' stress levels. Objective; To determine the relationship between family support and peer support with stress levels in Bachelor of Nursing students in facing their final assignment at Aisyiyah University of Surakarta. Methods; This research uses correlation analytics with a cross sectional approach. Sampling used random sampling with a total of 53 respondents with an instrument in the form of a questionnaire. The normality test used the Kolmogorov Smirnov Test and analyzed using the Spearman Rank Test. Results; There is a significant relationship between family support and stress levels and there is a significant relationship between peer support and stress levels. Conclusion; The relationship between family support and stress levels and the relationship between peer support and stress levels are not unidirectional, meaning that if family support is high then stress levels are low and vice versa.